Understanding emerging epidemics social and political approaches - Mukherjea, Ananya (Bingley, U.K. : Emerald, 2010)
This volume focuses on the contributions that social scientists can make to understanding emerging epidemics, their impact, the threats they pose, and their social and political contexts. While many of the international articles focus on infectious disease, some discussion is given to treating psychiatric epidemics and the analysis of the political and cultural meanings that epidemics have. A sociological volume on emerging epidemics, covering psychiatric or psychological diseases as well as infectious disease is long overdue and topics included here are as wide ranging as: bipolar disorder; obesity; malaria; HIV/AIDS; SARS; West Nile Virus; pandemic influenzas; deviance; depression; ADHD; Alzheimer's; and autism. This valuable reference tool empirically examines emerging epidemics themselves and offers a theoretical analysis of the use of epidemics and epidemiology as frameworks for understanding these phenomena. It will appeal to a broad audience of readers of researchers and practitioners in this field, ranging from those involved in public health policy, human security and community health to medical sociologists and other scientists working in health and medicine.
Introduction / Ananya Murkherjea -- Capitalism is making us sick : poverty, illness and the SARS crisis in Toronto / Jeffrey Shantz -- False perceptions and falciparum / Danae Roumis -- Policy, polity and the HIV crisis in emerging economies : India and Russia compared / Tinaz Pavri, Thomas Rotnem -- The concept of emerging infectious disease revisited / Márcia Grisotti, Fernando Dias de Avila-Pires -- Sounding a public health alarm : producing West Nile virus as a newly emerging infectious disease epidemic / Maya Gislason -- Emerging and concentrated HIV/AIDS epidemics and windows of opportunity : prevention and policy pitfalls / Shari L. Dworkin -- The social politics of pandemic influenzas : the question of (permeable) international, inter-species, and interpersonal boundaries / Ananya Mukherjea -- The poetics of American circumcision on the margins of medical necessity / Daniel Skinner -- Of rebels, conformists, and innovators : applying Merton's typology to explore an effective home care policy for the emerging Alzheimer's epidemic / William Cabin -- Promoted by Hong Tao, the Chlamydia / Frederick Attenborough -- The rhetoric of science and statistics in claims of an Autism epidemic / Victor W. Perez -- Bipolar disorder and the medicalization of mood : an epidemics of diagnosis? / Antonio Maturo -- What epidemic? : the social construction of bipolar epidemics / Kathryn Burrows -- The depression epidemic : how shifting definitions and industry practices shape perceptions of depression prevalence in the United States / Sara Kuppin -- Biomedicalizing metal illness : the case of attention deficit disorder / Manuel Vallée -- Contagious youth : deviance and the management of youth sociality / Michael Jolley -- A social change model of the obesity epidemic / Deborah A. Sullivan -- Who says obesity is an epidemic? : how excess weight became an American health crisis . Hanna Grol-Prokopczyk -- 'Who are you calling "fat"?' : the social construction of the obesity epidemic / Alana J. Hermiston.
Print version record
Keywords: Social Science -- Sociology -- General; Epidemiology & medical statistics; Epidemics -- Social aspects